ANALISIS ERGONOMI BEBAN KERJA FISIK TERHADAP STRES DAN KINERJA KARYAWAN PT. RIFANSI DWI PUTRA DURI - Yeni Yeni; Iwan Nauli Daulay; Anggia Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Companies that have competent employees strongly support the success of the company, where the company can compete with other companies. The performance of the company depends on the good and bad performance of employees, to see the performance of employees one of them by looking at the physical workload felt by employees during work that impact stress and make employee performance is not in accordance with the expected company. This study aims to determine the effect of physical workload on job stress and employee performance at PT. Rifansi Dwi Putra Duri. The population in this study covers all employees at PT. Rifansi Dwi Putra Duri which amounts to 120 people. The sampling technique chosen in this research is using census method, to test the hypothesis in this research is to use path analysis (path analysis) with the help of SPSS program. The results showed that: There is a negative influence and significant physical workload on the performance of employees of PT. Rifansi Dwi Putra Duri. There is a negative influence and significant job stress on the performance of employees of PT. Rifansi Dwi Putra Duri. There is a positive and significant influence between the physical workload on employee work stress PT. Rifansi Dwi Putra Duri. There is a significant indirect influence between the physical workload on performance through employee work stress PT. Rifansi Dwi Putra Duri.Keywords : Physical Workload, Job Stress, Employee Performance